(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2017)
The general aim of this article is to carry out a study about recalls, memory and gender about male polygamy, in a non-hegemonic cultural area made up of a cultural diversity which comprises the mapuche culture, sometimes visible in urban areas and sometimes not so tangible. The theoretical perspectives which have guided our work fit a framework in which recalls are considered to be individual and social, and are used to generate memories in which genre is included. We also mean to bear in mind the outlines which give fundamental importance to mimicry, in the process of reminisce -which is always from the present- as well as in the mecanisms which lead to consider the family assembly process, on which the model to imitate is the heterosexual monogamic couple. The method used is the qualitative ethnographic one, the documents to be analised have arisen from orality and participant observation in adults’ literacy courses. The temporal and special dimensions are given by a field work carried out between 1995 and 2013 in Bahía Blanca.